If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(7g + 2) = 32 Reorder the terms: -3(2 + 7g) = 32 (2 * -3 + 7g * -3) = 32 (-6 + -21g) = 32 Solving -6 + -21g = 32 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + -21g = 32 + 6 Combine like terms: -6 + 6 = 0 0 + -21g = 32 + 6 -21g = 32 + 6 Combine like terms: 32 + 6 = 38 -21g = 38 Divide each side by '-21'. g = -1.80952381 Simplifying g = -1.80952381
| f=8f+14 | | 6y(3+2)-23y=42 | | 2z+35=7z | | F(x)=z^3-14x^2+49 | | 2d=8d+36 | | -t-9=2t | | x^2+3x-1=2x+1 | | 2x+1=x^2+x-11 | | 7-5x+6x=-2 | | cosx-0.5x=1.0947 | | -7f+30=3f | | 13=3x-6x+1 | | -x+2+7x=26 | | 24=4x+6x-6 | | 5(2)+5(x)=15 | | -2r^5=54r^2 | | z^4+3z^2+1=0 | | 6v+5u=x | | 4x=-2x+54 | | 3x+10+4x=-67 | | -11=3a-2 | | 6a+7a-10a+16=14 | | =30x+20 | | -9h+9=-9 | | (2x-12)x(3x+15)=0 | | f(x)=-5x+8 | | c+54=-8c | | 5y+(86-x)=86+4y | | c+54=-84 | | 3x+11-4x=75 | | -x^3+4x^2-x+4=0 | | 9c-7=2c |